Combining hierarchical clustering and preference mapping differentiates consumer preference for dry aged mutton. (October 2022) - Hastie, Melindee; Torrico, Damir Dennis; Hepworth, Graham; Jacob, Robin; Ha, Minh; Polkinghorne, Rod; Warner, Robyn D.
Abstract: Dry ageing of mutton may enhance mutton's consumer appeal; however, consumer acceptance of mutton is heterogeneous. To identify which consumers prefer dry aged mutton, dry (DA) and wet aged mutton (WA) loin and topside were rated by consumers ( n = 540) for tenderness, juiciness, liking of flavour and overall liking on a 0–100 scale. Two predictive liking models were developed, utilising either consumer clusters (identified by agglomerative hierarchical clustering) which related to mutton liking and ageing method preference, or demographic factors. The cluster based model had the highest explanatory power. Cluster 1 ( n = 219) preferred DA ( p < 0.001), rating it 5.9 points higher than WA, cluster 2 ( n = 235) had no ageing method preference ( p > 0.05), and cluster 3 ( n = 79) preferred WA ( p < 0.001), rating WA liking 8.3 points higher than DA. Cluster characterisation identified some differences between clusters that may relate to consumer ethnicity and familiarity with mutton. Highlights: Three consumer clusters identified by agglomerative hierarchical clustering. External preference mapping indicate clusters differ in ageing method preference. Cluster based liking model had higher explanatory power than demographic based.